Diagnosis, management and prevention of Candida auris in hospitals: position statement of the Australasian Society for Infectious Diseases. Issue 10 (10th October 2019) - Ong, Chong W.; Chen, Sharon C.‐A.; Clark, Julia E.; Halliday, Catriona L.; Kidd, Sarah E.; Marriott, Deborah J.; Marshall, Caroline L.; Morris, Arthur J.; Morrissey, C. Orla; Roy, Rita; Slavin, Monica A.; Stewardson, Andrew J.; et al.
Abstract: Candida auris is an emerging drug‐resistant yeast responsible for hospital outbreaks. This statement reviews the evidence regarding diagnosis, treatment and prevention of this organism and provides consensus recommendations for clinicians and microbiologists in Australia and New Zealand. C . auris has been isolated in over 30 countries (including Australia). Bloodstream infections are the most frequently reported infections. Infections have crude mortality of 30–60%. Acquisition is generally healthcare‐associated and risks include underlying chronic disease, immunocompromise and presence of indwelling medical devices. C . auris may be misidentified by conventional phenotypic methods. Matrix‐assisted laser desorption ionisation time‐of‐flight mass spectrometry or sequencing of the internal transcribed spacer regions and/or the D1/D2 regions of the 28 S ribosomal DNA are therefore required for definitive laboratory identification. Antifungal drug resistance, particularly to fluconazole, is common, with variable resistance to amphotericin B and echinocandins. Echinocandins are currently recommended as first‐line therapy for infection in adults and children ≥2 months of age. For neonates and infants <2 months of age, amphotericin B deoxycholate is recommended. Healthcare facilities with C . auris should implement a multimodal control response. Colonised or infected patients should be isolated in single rooms with Standard and Contact Precautions. Close contacts, patients transferred from facilities with endemic C . auris or admitted following stay in overseas healthcare institutions should be pre‐emptively isolated and screened for colonisation. Composite swabs of the axilla and groin should be collected. Routine screening of healthcare workers and the environment is not recommended. Detergents and sporicidal disinfectants should be used for environmental decontamination.